The lateral neocortex is critical for contextual fear memory reconsolidation - de la Fuente, Verónica (2019)
Memories are a product of the concerted activity of many brain areas. Deregulation of consolidation and reprocessing of mnemonic traces that encode fearful experiences might result in fear-related psychopathologies. Here, we assessed how pre-established memories change with experience, particularly the labilization/reconsolidation of memory, using the whole-brain analysis technique of positron emission tomography in male mice. We found differences in glucose consumption in the lateral neocortex, hippocampus and amygdala in mice that underwent labilization/reconsolidation processes compared to animals that did not reactivate a fear memory. We used chemogenetics to obtain insight into the role of cortical areas in these phases of memory and found that the lateral neocortex is necessary for fear memory reconsolidation. Inhibition of lateral neocortex during reconsolidation altered glucose consumption levels in the amygdala. Using an optogenetic/neuronal recording-based strategy we observed that the lateral neocortex is functionally connected with the amygdala, which, along with retrograde labeling using fluorophore-conjugated cholera toxin subunit B, support a monosynaptic connection between these areas and poses this connection as a hot-spot in the circuits involved in reactivation of fear memories.